Removing the Checks and Balances That Hamper Democracy: Play and the Counter-hegemonic Contradictions of Grand Theft Auto IV - Ouellette, Marc (Eludamos: Journal for Computer Game Culture, 2010)
Grand Theft Auto IV provides an unparalleled opportunity to consider the outcomes when textual play and game play not only intersect, but operate in concert. Indeed, the two are inextricably linked to each other and to the social commentary which contributes to the game's story, humor, and thematic unity. This article considers the modes of textual play in Grand Theft Auto IV, as well as the locations and situations when players encounter them while playing the game. It also explores the subversive of potential of textual play as it relies on and departs from game play, and attempts to reconcile whether or not the success of such motives hinges on the very act of playing a game, or if the specific game (and its franchise) overdetermine the result.